Enhanced bioelectrochemical performance by NiCoAl-LDH/MXene hybrid as cathode catalyst for microbial fuel cell. (19th February 2023) - Chen, Junfeng; Zhang, Yiwen; Wu, Yiqun; Wang, Jingyu; Zhao, Yongyue; Wang, Mingkun; Yang, Jiaqi; Liu, Jinyu; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Abstract: In this work, NiCoAl-layered double hydroxide (LDH)/MXene was successfully prepared through straightforward hydrothermal method. NiCoAl-LDH was tightly and uniformly coated on MXene, forming a kind of porous structure. NiCoAl-LDH/MXene exhibited the (002) (012) (105) (100) crystal planes of hydrotalcite reflection. NiCoAl-LDH/MXene also showed superior catalytic oxygen reduction reaction (ORR) in response current according to electrochemical test (cyclic voltammetry (CV) etc.). The maximum power density and output voltage of NiCoAl-LDH/MXene as cathode in microbial fuel cell (MFC) was 362.404 mW/m 2 and 450 mV, respectively, which was 1.54 times of MXene-MFC (234.256 mW/m 2 ) and 1.71 times of NiCoAl-LDH-MFC (211.56 mW/m 2 ). The results indicated that NiCoAl-LDH/MXene was a kind of potential cathode catalyst for MFC and was full of future application. Graphical abstract: Image 1 Highlights: NiCoAl-LDH/MXene-MFC was synthesized by a simple hydrothermal method. Multi-layer NiCoAl-LDH and MXene structure enhanced electrochemical performance. NiCoAl-LDH/MXene had large active sites, rate performance and cycle stability. Maximum power density produced by MFC was 362.404 mW/m 2 .